The effect of participation in the Ugandan National Agricultural Advisory Services on willingness to pay for extension services - James, P.A.; Smart, J.C.; Smith, J.; Bulling, M.T.; Beed, Fenton D.; Luwandagga, D. (2011)
Uganda’s National Agricultural Advisory Services (NAADS), established in 2001, is a demand-driven extension program for developing farmer organizations and improving farmer production and welfare. The program is expected to be 50% client funded after 25 years. However, varying returns to extension services and inconclusive evidence about their effectiveness suggest that farmers may not be willing to pay for these services. Using a choice experiment, this study found that longer participation in NAADS increased farmers’ willingness to pay and that NAADS had a cost beneficial effect at farm level. The findings suggest that farmers are willing to pay for extension advice (US$0.20, which is higher than that found for most other African extension systems) if they see they are given good information, though they should not be asked to pay the full cost. Longer association with NAADS promoted the adoption of new crops, reduced the vulnerability of farms by increasing technology adoption and improved farmer welfare.